Shikonin Prolongs Allograft Survival via Induction of CD4+FoxP3+ Regulatory T Cells - Zeng, Qiaohuang; Qiu, Feifei; Chen, Yuchao; Liu, Cuihua; Liu, Huazhen; Liang, Chun-Ling; Zhang, Qunfang; Dai, Zhenhua (Frontiers in Immunology, 2019)
A transplanted organ is usually rejected without any major immunosuppressive treatment because of vigorous alloimmune responsiveness. However, continuous global immunosuppression may cause severe side effects, including nephrotoxicity, tumors and infections. Therefore, it is necessary to seek novel immunosuppressive agents, especially natural ingredients that may provide sufficient efficacy in immunosuppression with minimal side effects. Shikonin is a bioactive naphthoquinone pigment, an ingredient originally extracted from the root of Lithospermum erythrorhizon. Previous studies have shown that shikonin regulates immunity and exerts anti-inﬂammatory effects. In particular, it can ameliorate arthritis in animal models. However, it is unclear whether shikonin inhibits alloimmunity or allograft rejection. In this study and for the first time, we demonstrated that shikonin significantly prolonged the survival of skin allografts in wild-type mice. Shikonin increased the frequencies of CD4+Foxp3+ regulatory T cells (Tregs) post-transplantation and induced CD4+Foxp3+ Tregs in vitro as well. Importantly, depleting the Tregs abrogated the extension of skin allograft survival induced by shikonin. It also decreased the frequencies of CD8+CD44highCD62Llow effector T cells and CD11c+CD80+/ CD11c+CD86+ mature DCs after transplantation. Moreover, we found that shikonin inhibited the proliferation of T cells in vitro and suppressed their mTOR signaling. It also reduced the gene expression of pro-inﬂammatory cytokines, including IFNγ, IL-6, TNFα and IL-17A, while increasing the gene expression of anti-inflammatory mediators IL-10, TGF-β1 and indoleamine-2, 3-dioxygenase (IDO) in skin allografts. Further, shikonin downregulated IDO protein expression in skin allografts and DCs in vitro. Taken together, shikonin inhibits allograft rejection via upregulating CD4+Foxp3+ Tregs. Thus, shikonin is a novel immunosuppressant that could be potentially used in clinical transplantation.